Analysis and Control for Heavy Equipment Spare Parts Inventory in the Nickel Mining Industry - Pardede, Sri Rahayu; Vanany, Iwan (IPTEK Journal of Proceedings Series, 2020)
In the mining industry, analyzing, and controlling the spare parts inventory is important activities and need special attention from the company. The high production cost of the mining industry, including spare parts and shortages costs affects the financial and operational aspects of the company. Spare parts inventory management policy is critical to increase the service level and minimize spare parts cost. In this mining case study, the out of stock incidents in the heavy equipment spare parts were often occurring and significantly affecting the performance of maintenance and operations. The purpose of this study is to determine minimum stock (safety stock) and maximum stock to reduce overstocks and reduce the number of stocks out in spare parts inventory and as well as inventory cost. The method used to solve the problem is economic order quantity (EOQ) and continuous review control (S, s) to determine the minimum and maximum stocks. Determining the combination of S and s has a major impact on the success of inventory control. Substitution parts are subdivided into alphabetical values to determine their significance. As a result of calculating inventory value using EOQ and S, s will get the highest inventory value to reduce inventory costs.